A review on the reporting and assessment of adverse effects associated with high-definition transcranial direct current stimulation - Carther-Krone, Tiffany; Ko, Ji Hyun (Frontiers in Human Neuroscience, 2025)
BackgroundHigh-definition transcranial direct current stimulation (HD-tDCS) is a non-invasive brain stimulation technique that offers increased spatial precision compared to conventional tDCS. As its use has expanded across research and clinical settings, there has been increasing interest in understanding its safety and tolerability.ObjectiveThis review summarizes adverse events related to HD-tDCS in both healthy and clinical populations, focusing on how stimulation intensity, session frequency, and polarity influence tolerability.ResultsIn healthy populations, HD-tDCS is most often administered at 1–2 mA for 20 min. The most reported adverse events include tingling, itching and burning localized to the site of stimulation, typically described as mild or transient. Studies comparing active and sham stimulation generally report no significant differences in adverse event frequency or intensity, even at higher intensities of 2–3 mA. Reports of severe adverse events are rare, and participant dropout due to discomfort is uncommon. Multi-session protocols show similar safety profiles, suggesting that repeated stimulation does not increase adverse effects. In clinical populations HD-tDCS is typically delivered across multiple sessions. Reported adverse events are mild and transient, with few reports of severe outcomes. Polarity-specific comparisons suggest that anodal and cathodal stimulation are similarly tolerated, with no notable differences in adverse event profiles.ConclusionOverall, current evidence indicates that HD-tDCS is a safe and well-tolerated technique across diverse populations and stimulation parameters. Continued use of standardized adverse event reporting will be important to further confirm these findings as clinical application broaden.